Contextual Environment-Based Science Learning: Contribution of Local Learning Resources, Student Activeness, Teacher Academic Leadership, and School Culture - Djoko Sri Bimo; Fadloli; Cicilia Clara Devi Anggraini (MIMBAR PGSD Undiksha, 2026)
The research is grounded in the importance of utilizing the environment as a natural laboratory and its connection to the socio-cultural context of primary school students. This study aims to analyze the contribution of contextual science learning based on the local environment to improve learning outcomes through four key variables: local learning resources, student activeness, academic leadership of teachers, and school culture. This study employed a mixed-method approach with a sequential explanatory design. The population consisted of fifth-grade students and science teachers at public elementary schools. A purposive sampling technique was used to select six representative schools. Quantitative instruments included a Likert-scale questionnaire, while qualitative instruments comprised in-depth interviews, observations, and documentation. The findings revealed that all four variables positively contributed to the effectiveness of environment-based science learning. Local learning resources enhanced content relevance, student activeness promoted cognitive engagement, academic leadership fostered instructional innovation, and school culture supported a conducive learning environment. These findings underscore the importance of integrating pedagogical elements with local contextual values in science education. In conclusion, contextual science learning supported by holistic school components significantly improves both the process and outcomes of science learning at the elementary level. The implications of this study offer valuable input for curriculum development and teacher training programs grounded in local potential.